Cristo de las Américas. El diálogo entre Thomas Merton y Pablo Antonio Cuadra en sus cartas (2021)
In April 1958, the Nicaraguan poet Pablo Antonio Cuadra (1912-2002) personally met the American poet Thomas Merton (1915-1968) during a visit to his cousin Ernesto Cardenal, who was Merton's newcomer, we do not show the Trappist of Gethsemane. Kentucky, United States. Between the two writers there was a sporadic and fruitful correspondence linked to the unexpected and sudden death of Merton in Bangkok in 1968, in which they exchanged literary projects, confidences and artistic and spiritual insights. Unpublished so far, this correspondence allows us to spy on their intimidation and highlight the intertwined aspirations of Christian poets and authors. This article is part of the epistolary dialogue between Thomas Merton and Pablo Antonio Cuadra.